PENGEMBANGAN MODEL MANAJEMEN TERPADU PENDIDIKAN ISLAM BERBASIS EVALUASI KINERJA DAN KEY PERFORMANCE INDICATOR (KPI) UNTUK PENINGKATAN TATA KELOLA KELEMBAGAAN - Jasuli Jasuli; Achmad Muhlis (Jurnal Manajemen Pendidikan, 2026)
This study aims to develop an integrated management model for Islamic education based on performance evaluation and Key Performance Indicators (KPIs) to enhance the quality of institutional governance. The background of this study is rooted in the growing demand to improve the quality of Islamic educational institutions amid globalization and digital transformation, which require more effective, measurable, and performance-based management systems. This study employed a qualitative approach using a library research method by examining various relevant books, journal articles, and academic documents. The findings reveal that integrated management in Islamic education should holistically combine Islamic values with modern management approaches. Performance evaluation serves as a strategic instrument for measuring and improving organizational effectiveness, while Key Performance Indicators (KPIs) function as specific and measurable indicators for objectively assessing organizational performance. The integration of performance evaluation and KPIs within a unified management system creates a systematic management cycle encompassing planning, implementation, monitoring, evaluation, and data-driven follow-up actions. The implementation of this model contributes to improved accountability, transparency, efficiency in resource management, and the professionalism of human resources within Islamic educational institutions.